No-prep semidirect composite resin veneer : a step-by-step case report in a deciduous canine with a one-year follow-up = Carilla de resina semidirecta sin preparación : un reporte paso a paso en un canino deciduo con seguimiento de un año - Durán Ojeda, Gerardo
The presence of deciduous canines in adulthood may be of aesthetic concern for patients. Many clinical alternatives include surgical and orthodontic treatment. Since patients search for highly esthetic results and more conservative alternatives, the present clinical report describes a treatment for deciduous canine through an indirect composite resin veneer and an indirect composite resin fragment restoration in a premolar to improve esthetic outcomes with a one-year follow up.